Aspek Nonfarmakologis Pengobatan Albendazol Pada Cacingan: Review Sistematis - Meivie Jeanne Tumiwa; Grace Debbie Kandou; Billy Johnson Kepel (Universitas Sam Ratulangi, 2021)
Background: Treatment efforts with albendazole have been implemented for a long time but intestinal worms are still a problem in Indonesia and even in the world, there are aspects or non-pharmacological factors that affect the treatment of intestinal worms with albendazole. The purpose of this study was to determine the nonpharmacological aspects of albendazole treatment in intestinal worms. Method: This research is a systematic review. Sources of research articles were taken from the PubMed database, Science direct, Wiley online library and Google scholar, with the keywords